Modern state of occupational injury at meat industry enterprises of Ukraine - Evtushenko, Olga; Evtushenko, Oleg (My University, 2014)
The stage of industrial injuries in the meat industry of Ukraine during 2003-2013 is analyzed. Identified the most common traumatic factors and jobs | in the meat industry of Ukraine. Results of research can be used in improving management decisions projects that can provide safe working conditions on Meat Processing Plants. Проаналізовано стан виробничого травматизму у м'ясній промисловості України за період 2003…2013 р. Виявлені найбільш поширені травмуючі фактори і професії в м'ясній промисловості України. Проанализировано состояние производственного травматизма в мясной промышленности Украины за период 2003...2013 г. Выявлены наиболее распространенные травмирующие факторы и профессии в мясной промышленности Украины.
Keywords: industrial traumatism; accident; safety; work; виробничий травматизм; нещасний випадок; безпека; праця; кафедра екології та екоменеджменту